Fluconazole for Hypercortisolism in Cushing’s Disease: A Case Report and Literature Review - Zhao, Yiming; Liang, Weiwei; Cai, Feng; Wu, Qun; Wang, Yongjian (Frontiers in Endocrinology, 2020)
Background: Cushing’s disease is associated with an increased risk of pulmonary fungal infection, which could be a relative contraindication for pituitary adenoma excision surgery. Case: We report a case of a patient with Cushing’s disease and pulmonary Cryptococcus neoformans. A 48-year-old woman was admitted to our hospital because of moon face and edema. Laboratory and radiological findings suggested a diagnosis of Cushing’s disease and pulmonary cryptococcus infection. Fluconazole 400mg per day was administered intravenously and continued orally for 3 months. Both cryptococcus infection and hypercortisolism relieved and transsphenoidal resection was performed. Conclusion: Cushing’s disease can be effectively treated with fluconazole to normalize cortisol concentration prior to pituitary surgery. Fluconazole is an alternative treatment especially in Cushing’s disease patients with cryptococcal pneumonia.